Responses of two genotypes of lambs on the infection of Haemonchus contortus and the level of energy supplements - Ginting, Simon P; Batubara, Aron; Romjali, Endang; Rangkuti, M; ., Subandriyo (Indonesian Animal Sciences Society, 1999)
A study was conducted to evaluate the responses of lambs on the infection of Haemonchus contortus and the level of energy supplements. Forty eight male lambs, 3-4 months old were used in a factorial experimental design (2x2x2) which lasted for 9 weeks. The factors were breed (Local Sumatra and Sungai Putih: 50% Local Sumatra, 25% St. Croix; 25% Barbados Blackbelly), level of Haemonchus infection (3,000 L3 and 1,500 L3 per week) and level of energy supplement (2,900 kcal/kg DM and 2,300 kcal/kg DM). Infection at 3,000 L3 decreased (P<0.05) ADG of lambs of both energy levels. An extremely low ADG (10-16 g) was observed in 3000 L3 group given low energy level. Body condition of lambs fed high energy level was constant over the experiment, but it decreased at the rate of 0.9 to 1.1 unit at the low energy supplement. EPG was higher (P>0.001) in the 3000 L3 group, was lower (P<0.05) in the Local Sumatra, but not affected (P>0.10) by energy level. PCV was not affected (P>0.10) by infection levels, but lower (P<0.01) in the low energy group or in the St Croix crosses. Eosinophil and serum protein concentration were not affected by energy and infection level, but they were higher (P<0.01) in the local Sumatra. It was concluded that strong effects of level of infection and genotype was detected to influence the impact of Haemonchus infection in lambs. However, the effect of energy levels was less consistent as judged from the EPG, PCV, eosinophil and serum protein data. Â Key words : Energy level, genotype, infection level, Haemonchus contortus, lambs